2020
DOI: 10.1007/s00125-020-05103-w
|View full text |Cite
|
Sign up to set email alerts
|

Akap1 deficiency exacerbates diabetic cardiomyopathy in mice by NDUFS1-mediated mitochondrial dysfunction and apoptosis

Abstract: Aims/hypothesis Diabetic cardiomyopathy, characterised by increased oxidative damage and mitochondrial dysfunction, contributes to the increased risk of heart failure in individuals with diabetes. Considering that A-kinase anchoring protein 121 (AKAP1) is localised in the mitochondrial outer membrane and plays key roles in the regulation of mitochondrial function, this study aimed to investigate the role of AKAP1 in diabetic cardiomyopathy and explore its underlying mechanisms. Methods Loss-and gain-of-functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 40 publications
0
52
0
Order By: Relevance
“…Downregulation of CMKLR1 suppressed cardiac cell death in DCM rats. Although apoptosis and necrosis are the forms of cell death that are normally detected in DCM patients (Chowdhry et al, 2007;D'Arcy, 2019;Ge et al, 2019;Qi et al, 2020) recent studie have shown that other types of cell death, such as pyroptosis, are also found in DCM (Wang X. et al, 2019). Pyroptosis is a type of programmed cell death that is commonly induced by caspase-1 activation, and is characterized by pore formation on the plasma membrane, cell swelling, nuclear DNA damage, and release of intracellular inflammatory content (Liu et al, 2016;Lacey et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of CMKLR1 suppressed cardiac cell death in DCM rats. Although apoptosis and necrosis are the forms of cell death that are normally detected in DCM patients (Chowdhry et al, 2007;D'Arcy, 2019;Ge et al, 2019;Qi et al, 2020) recent studie have shown that other types of cell death, such as pyroptosis, are also found in DCM (Wang X. et al, 2019). Pyroptosis is a type of programmed cell death that is commonly induced by caspase-1 activation, and is characterized by pore formation on the plasma membrane, cell swelling, nuclear DNA damage, and release of intracellular inflammatory content (Liu et al, 2016;Lacey et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term hyperglycemia is supposed to induce damage and cause subsequent apoptosis in cardiomyocytes [33,34]. It has been reported that cardiomyocyte apoptosis exacerbated the development of DCM [35][36][37]. Our previous research found that persistent hyperglycemia aggravated endoplasmic reticulum stress response of cardiomyocytes, which in turn led to cell apoptosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyocyte apoptosis is a key component of SIC ( Cai et al, 2020 ; Qi et al, 2020 ), and inhibiting cardiomyocyte apoptosis can effectively improve myocardial injury in sepsis ( Hong et al, 2021 ). Mitochondrial damage activates cardiomyocyte apoptosis, and pro-apoptotic proteins Bax and Bad translocate to the mitochondrial outer membrane and interact with it, causing the opening of the mitochondrial permeability transition pore (MPTP).…”
Section: Discussionmentioning
confidence: 99%